2012
DOI: 10.4236/ojn.2012.22015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, skill and attitude of oncology nurses in chemotherapy administration in tertiary hospital Pakistan

Abstract: Objective: To measure the levels of nurse’s knowledge and attitude after the conduct of education session regarding chemotherapy administration and management. Methodology: This research study was conducted at two oncology units of tertiary Hospital Rawalpindi. A prepost test intervention study design was used on 35 nurses by using Verity’s tools. Results: The mean scores of knowledge were calculated by Cochran’s Q test showed that knowledge scores have significantly increased with ‘educational training’ (p va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
29
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 21 publications
11
29
2
2
Order By: Relevance
“…On top of that, the interventions had led to the change of nurses' attitude towards certain safety-related issues. The confidence level among the nurses to handle cytotoxic drugs safely after the interventions (79.2%) was comparable to the findings in a recent Pakistani study (77%) (Khan et al, 2012). Besides that, their awareness on long-term hazardous effects due to the occupational exposure was significantly improved.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…On top of that, the interventions had led to the change of nurses' attitude towards certain safety-related issues. The confidence level among the nurses to handle cytotoxic drugs safely after the interventions (79.2%) was comparable to the findings in a recent Pakistani study (77%) (Khan et al, 2012). Besides that, their awareness on long-term hazardous effects due to the occupational exposure was significantly improved.…”
Section: Discussionsupporting
confidence: 81%
“…The percentage of nurses who believed that using PPE was not necessary during cytotoxic drug handling was also tremendously decreased. This finding is again comparable to the achievement of Pakistani nurses (Khan et al, 2012). Meanwhile, their levels of tolerance towards their own and co-workers' improper practices were alleviated.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The current study in line with the findings of the study by Khan et al ; ( 2012) [35] indicated that oncology nurses had poor knowledge and skills. Unsafe chemotherapy administration considered especially when nurses had no updated and advanced knowledge and not competent in skills of administration.…”
Section: Similar To Findings Of Abbasy (2013 ) [21] Gauski (2016)supporting
confidence: 91%